Benjamín I. SCHWARTZ (ed.), Reflections on the May Fourth Movement: a symposium Cambridge, Mass., Harvard University Press, 1972, Harvard East Asian Monographes. Nº 44, 132 pp. - -, - (Estudios de Asia y África, 1980)
-